Plan de mejoramiento en la calidad del servicio prestado por una curaduría urbana de Bogotá (2016)
At present, the State has focused its efforts on improving service in companies and organizations that fulfill public functions, so it is of great importance that these are organized by processes and that they have an internal control area in their strategic structure. that is in charge of improving the customer service, satisfying their needs and improving the image of the public servant. The quality of service is defined as making things and people work well from the beginning, to open their minds to the idea that it is always possible to improve any task that is carried out.